Exposure assessment and micronuclei induction in populations exposed to electronic waste in South-West Nigeria - Igharo, Osaretin Godwin; Akpata, C.B.N.; Aikpitanyi-Iduitua, G. A.; Oshilonyah, L. U.; Ola-Davies, O.E.; Anetor, J. I. (Universa Medicina, 2024)
BACKGROUNDInformal electronic waste (e-waste) reprocessing in Nigeria is reportedly substantial in Africa, putting the growing exposed population at high risk of metal toxicity. This study aimed to investigate the existence of chromosomal aberration in the growing e-waste exposed populations in Nigeria, using induction of micronuclei (MN) expression in peripheral blood as an indicator. METHODSIn this cross-sectional study, 632 consenting participants were recruited from South-West Nigeria, consisting of 381 e-waste workers (EWW), 120 environmental e-waste exposed participants (EEP) and 131 age-matched unexposed participants (UP) serving as controls. A validated structured questionnaire was used to assess exposure pattern while frequency of micronucleated polychromatic erythrocytes (MNPCE)/1000PCE in peripheral blood film was determined by modified micronucleus assay. RESULTSA duration of exposure of ³5 years and exposure frequency ³6 hours/day; 6 days/week (9360 hours in any 5-year duration) was observed in both EWW and EEP. Routes of exposure observed in EWW entailed eyes, oral cavity, nasal cavity and skin. EWW that used personal protective equipment (PPE) while working was barely 10.24% while non-PPE users constituted the majority (89.76%) of the studied population. Frequency of MNPCE)/1000PCE in EWW (22.70 ± 0.15) was significantly higher than in EEP (4.17 ± 0.28), which in turn was significantly higher than the lowest frequency (0.99 ± 0.76) observed in UP (p<0.001). CONCLUSIONThe observed exposure pattern and the comparatively higher MN induction in the e-waste populations may suggest risk of significant cytogenetic damage and aberrant chromosomal changes associated with occupational e-waste reprocessing in Nigeria.